Monoclonal antibody against macrophage colony‐stimulating factor suppresses circulating monocytes and tissue macrophage function but does not alter cell infiltration/activation in cutaneous lesions or clinical outcomes in patients with cutaneous lupus erythematosus. (9th November 2015) - Masek‐Hammerman, K.; Peeva, E.; Ahmad, A.; Menon, S.; Afsharvand, M.; Peng Qu, R.; Cheng, J. B.; Syed, J.; Zhan, Y.; O'Neil, S. P.; Pleasic‐Williams, S.; Cox, L.A.; et al.
Summary: This study's objective was to assess the effects of PD‐0360324, a fully human immunoglobulin G2 monoclonal antibody against macrophage colony‐stimulating factor in cutaneous lupus erythematosus (CLE). Patients with active subacute CLE or discoid lupus erythematosus were randomized to receive 100 or 150 mg PD‐0360324 or placebo via intravenous infusion every 2 weeks for 3 months. Blood and urine samples were obtained pre‐ and post‐treatment to analyse pharmacokinetics and pharmacodynamic changes in CD14 + CD16 + monocytes, urinary N‐terminal telopeptide (uNTX), alanine/aspartate aminotransferases (ALT/AST) and creatine kinase (CK); tissue biopsy samples were taken to evaluate macrophage populations and T cells using immunohistochemistry. Clinical efficacy assessments included the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). Among 28 randomized/analysed patients, peak/trough plasma concentrations increased in a greater‐than‐dose‐proportional manner with dose increases from 100 to 150 mg. Statistically significant differences were observed between active treatment and placebo groups in changes from baseline in CD14 + CD16 + cells, uNTX, ALT, AST and CK levels at most time‐points. The numbers, density and activation states of tissue macrophages and T cells did not change from baseline to treatment end. No between‐group differences were seen in CLASI. Patients receiving PD‐0360324 reported significantly more adverse events than those receiving placebo, but no serious adverse events. In patients with CLE, 100 and 150 mg PD‐0360324 every 2 weeks for 3 months suppressed a subset of circulating monocytes and altered activity of some tissue macrophages without affecting cell populations in CLE skin lesions or improving clinical end‐points.